Comparison of enzyme-linked immunosorbent assay, radioimmunoassay, complement fixation, anticomplement immunofluorescence and passive haemagglutination techniques for detecting cytomegalovirus IgG antibody. Issue 12 (December 1982) - Booth, J C; Hannington, G; Bakir, T M; Stern, H; Kangro, H; Griffiths, P D; Heath, R B
Abstract : The radioimmunoassay (RIA) and enzyme-linked immunosorbent assay (ELISA) techniques were found to be comparable in sensitivity and specificity for detecting cytomegalovirus IgG antibody, and 10 to 100 times more sensitive than complement-fixation (CF), anticomplement immunofluorescence (ACIF) and passive haemagglutination (PHA). In screening tests for antibody, the frequency of false-positive and -negative results was 0.6% for RIA and ELISA, 1.5% for CF, 1.6% for ACIF and 3.6% for PHA. PHA was the least satisfactory test, largely because of technical problems. Cytomegalovirus (CMV) infection is an important cause of congenital brain damage and is also a major complication of both prolonged immunosuppressive therapy, especially in patients with organ transplants, and multi-donor blood transfusions. For serological diagnosis of infection, as well as for screening for antibody in patients and in blood donors, the solid-phase indirect radioimmunoassay (RIA) and enzyme-linked immunosorbent assay (ELISA) techniques offer distinct improvements in sensitivity over previous methods. Although the principle of both tests, based on the detection of antigen-antibody reactions by means of a labelled anti-antibody, is the same, each possesses its own particular technical advantages and disadvantages, and both require their own expensive equipment for the reading of the results. There is still a lack of data on how they compare in sensitivity and specificity. The present study was undertaken to compare the two methods for the detection of CMV IgG and to evaluate them against the older techniques of complement-fixation (CF), passive haemagglutination (PHA) and anticomplement immunofluorescence (ACIF).